2021
DOI: 10.1111/1750-3841.15637
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity ultrasound improves threadfin bream surimi gelation at low NaCl contents

Abstract: Effects of high‐intensity ultrasound (HIU) treatments on gelation of threadfin bream (Nemipterus spp.) surimi at various NaCl contents (0.5, 1, and 2% NaCl) were investigated. Protein extractability at 0.5% NaCl was increased with the ultrasonic intensity (p < 0.05). At all tested NaCl contents, reactive sulfhydryl group (SH) content and surface hydrophobicity of the surimi pastes were increased after HIU treatments and were accompanied by a decrease in the Ca2+‐ATPase activity and total SH content, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In fact, this increase in β-sheet content reflected an enhancement of the number of hydrogen bonds which could maintain stable protein conformation and strengthen the intermolecular forces between proteins so as to form an ordered gel network structure [14] , [40] . Similar results were reported by Tang et al [32] who concluded that surimi gels of threadfin bream at 2% NaCl content had less α-helix but more β-sheet, thus confirming that high NaCl level induce a higher degree of unfolding in proteins. Xiong et al [2] reported that the protein secondary structures in bighead carp surimi gels presented a higher β-sheet content at 3% NaCl addition compared with 0.5% NaCl addition.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…In fact, this increase in β-sheet content reflected an enhancement of the number of hydrogen bonds which could maintain stable protein conformation and strengthen the intermolecular forces between proteins so as to form an ordered gel network structure [14] , [40] . Similar results were reported by Tang et al [32] who concluded that surimi gels of threadfin bream at 2% NaCl content had less α-helix but more β-sheet, thus confirming that high NaCl level induce a higher degree of unfolding in proteins. Xiong et al [2] reported that the protein secondary structures in bighead carp surimi gels presented a higher β-sheet content at 3% NaCl addition compared with 0.5% NaCl addition.…”
Section: Resultssupporting
confidence: 89%
“…Gao et al [25] reported that the deformation and breaking force of surimi gels were promoted as the NaCl content increased from 0% to 5%, and these results were consistent with ours. Similarly, Tang et al [32] also concluded that the gel strength of surimi with 0.5% NaCl addition was lower than that with a 2.0% NaCl addition.
Fig.
…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations